Improvement of retinal microvascular function after initiation of lipid-lowering therapy with PCSK9 inhibitors – an observational study. (14th October 2021) - Naegele, M; Raemy, Y; Barthelmes, J; Kreysing, L; Haider, T; Ruschitzka, F; Flammer, A J; Sudano, I
Abstract: Background: Hypercholesterolemia is associated with endothelial dysfunction. While good evidence exists for the beneficial endothelial effects of first-line lipid-lowering drugs (statins), less is known on the new class of proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. This is particularly true for the differential effects on micro- and macrovascular endothelial function and arterial stiffness. Purpose: The goal of this study was to study the change in retinal microvascular dysfunction, brachial artery endothelial function and arterial stiffness in high-risk cardiovascular risk patients before and after initiation of PCSK9 inhibitor therapy with alirocumab or evolocumab. Methods: In this prospective observational study, cardiovascular high-risk patients with a clinical indication for PCSK9 inhibitors were included for the measurement of retinal microvascular function (flicker light-induced dilatation of retinal arterioles and venules, FIDart and FIDven respectively; retinal arteriovenous ratio, AVR), brachial artery flow-mediated dilatation (FMD) and arterial stiffness (pulse wave velocity, PWV; augmentation index, AI). Measurements were performed at baseline, after 3 months and after 12 months of PCSK9 inhibitor therapy. The primary endpoint was the change in FIDart after 12 months of therapy compared to baseline. Results: We recruited 48 patients (mean age 57±11 years, 27% female, 81% coronary artery disease) which began treatment with alirocumab or evolocumab in our lipid outpatient clinic. 6 patients were excluded from the analysis (n=3 stopped due to side effects, n=1 stopped due to new metastatic cancer, n=1 moved abroad, n=1 no retinal vessel analysis possible). LDL cholesterol was reduced from 3.8±1.2 to 1.5±0.8 and 1.8±0.9 mmol/L at 3 and 12 months respectively (all p<0.001). There was no significant change in systolic blood pressure during therapy. The primary endpoint FIDart was significantly increased after 12 months of PCSK9 inhibitor therapy compared to baseline (3.4±2.3 vs. 2.6±1.6%, p=0.01). Among the secondary endpoints, augmentation index improved at 12 months vs. baseline (21±12 vs. 24±9%, p=0.03). No significant change was seen for FIDven, AVR, FMD and PWV after 3 and 12 months of therapy. Conclusion: In cardiovascular high-risk patients, PCSK9 inhibition is associated with an improvement of retinal microvascular function and augmentation index after one year of therapy. No effects were seen for macrovascular parameters such as FMD or PWV in our cohort. FUNDunding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): University Hospital Zurich, AGLA Grant (sponsored by Amgen)